Coexistence of tetragonal and cubic phase induced complex magnetic behaviour in CoMn2O4 nanoparticles - Rajput S.; Yadav M.; Dehury T.; Yadav A.K.; Sahoo P.K.; Rath C. (My University, 2025)
CoMn2O4, known for its extensive range of applications, has been subject to limited investigations regarding its structure dependent magnetic properties. Here, we have examined the structure dependent magnetic properties of CoMn2O4 nanoparticles synthesized through a facile coprecipitation technique and are characterized using x-ray diffractometer, x-ray photoelectron spectroscopy (XPS), RAMAN spectroscopy, transmission electron microscopy and magnetic measurements. Rietveld refinement of the x-ray diffraction pattern reveals the coexistence of 91.84% of tetragonal and 8.16% of cubic phase. The cation distribution for tetragonal and cubic phases are (Co0.94Mn0.06)[Co0.06Mn1.94]O4 and (Co0.04Mn0.96)[Co0.96Mn1.04]O4, respectively. While Raman spectra and selected area electron diffraction pattern confirm the spinel structure, both +2 and +3 oxidation states for Co and Mn confirmed by XPS further corroborate the cation distribution. Magnetic measurement shows two magnetic transitions, Tc1 at 165 K and Tc2 at 93 K corresponding to paramagnetic to a lower magnetically ordered ferrimagnetic state followed by a higher magnetically ordered ferrimagnetic state, respectively. While Tc1 is attributed to the cubic phase having inverse spinel structure, Tc2 corresponds to the tetragonal phase with normal spinel. In contrast to general temperature dependent H C observed in ferrimagnetic material, an unusual temperature dependent H C with high spontaneous exchange bias of 2.971 kOe and conventional exchange bias of 3.316 kOe at 50 K are observed. Interestingly, a high vertical magnetization shift (VMS) of 2.5 emu g−1 is observed at 5 K, attributed to the Yafet-Kittel spin structure of Mn3+ in the octahedral site. Such unusual results are discussed on the basis of competition between the non-collinear triangular spin canting configuration of Mn3+ cations of octahedral sites and collinear spins of tetrahedral site. The observed VMS has the potential to revolutionize the future of ultrahigh density magnetic recording technology. © 2023 IOP Publishing Ltd.